1999
DOI: 10.1080/10400435.1999.10131984
|View full text |Cite
|
Sign up to set email alerts
|

Wheelchair Seating Aids: How Satisfied Are Consumers?

Abstract: The purpose of this study was to evaluate user satisfaction with wheelchair seating aids. A modified version of the Quebec User Evaluation of Satisfaction with assistive Technology (QUEST ) was used to assess satisfaction of 24 subjects who owned a modular-type se a ting device integrated in a powered wheelchair. The results of this QUEST-based approach revealed that the variable comfort was identified as the most important consumer criterion yet it was evaluated as the least sa tis fyin g. There were statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…The fact that smaller angles of tilt-in-space were used possibly implies that this seating function was used more for functional and stable postures and comfort than for shifting weight or pressure management. Previous studies showed that comfort is a primary concern regarding the seating system and that people use smaller tilt-in-space angles to increase comfort [11,25]. Subjects in this study also reported that they accessed tilt-in-space to adjust posture for comfort.…”
Section: Discussionmentioning
confidence: 59%
“…The fact that smaller angles of tilt-in-space were used possibly implies that this seating function was used more for functional and stable postures and comfort than for shifting weight or pressure management. Previous studies showed that comfort is a primary concern regarding the seating system and that people use smaller tilt-in-space angles to increase comfort [11,25]. Subjects in this study also reported that they accessed tilt-in-space to adjust posture for comfort.…”
Section: Discussionmentioning
confidence: 59%
“…Vachon et al found that 32 elderly residents of long-term care facilities were most satisfied with the simplicity of use, safety, and effectiveness of their wheelchairs and least satisfied with the adjustability, comfort, weight, and follow-up services of their wheelchairs [23]. In WeissLambrou et al's study [30], users of power wheelchairs identified wheelchair comfort as the most important criteria, though comfort was the lowest rated variable in the study. Similarly, satisfaction with wheelchair comfort received a low rating in our study.…”
Section: Satisfaction Issuesmentioning
confidence: 95%
“…In a Canadian study by Weiss‐Lambrou, Tremblay, LeBlanc, Lacoste and Dansereau (1999) wheelchair users rated comfort as the most important factor affecting their satisfaction with their seating aids. The same raters selected comfort as the least satisfactory aspect of wheelchair use.…”
Section: Introductionmentioning
confidence: 99%